Hybrid multi-criteria framework to determine the hierarchy of hydropower reservoirs in India for floatovoltaic installation. (November 2022) - Puppala, Harish; Vasanthawada, Sri Ramana Saketh; Garlapati, Nagababu; Saini, Gaurav
Highlights: Estimated the floating solar potential of major hydropower reservoirs in India. Proposed hybrid multi-criteria framework to determine the hierarchy. Potential hydropower plant in each state for installing FSP plant is identified. Floatovoltaic potential of Madhya Pradesh is the highest among all the states. Abstract: Increasing the share of renewable energy power generation is imperative for the attainment of Sustainable Development Goal 7 (SDG-7). Though photovoltaic technology is a reliable renewable alternative in many countries, the land required to expand the installed capacity remained as a prime barrier. In this context, Floating Solar Panels (FSP), also popular as floatovoltaics, are identified as a viable alternative. Installation of floatovoltaics is in the nascent stages in many countries, especially in India, where photovoltaics are popular for harnessing solar energy. Research works addressing the FSP potential of hydropower reservoirs in India and determining their hierarchy to plan developmental works in phase wise manner are limited. This study analyses the FSP potential of all major hydropower reservoirs in India. National inventory data to facilitate floatovoltaic power estimates is created, and an active dashboard is hosted for better transparency and monitoring. Using the created geospatial database, the hierarchy of hydropower reservoirs is evaluated with the help of the proposed hybrid multi-criteria framework developed by integrating Shannon entropy and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) techniques. A wide range of governing parameters, such as (i) available area for installation, (ii) harnessable power, (iii) capacity factor, (iv) elevation, and (v) wind speed, are considered to evaluate the hydropower reservoirs. Overall dominance of each hydropower reservoir evaluated using the proposed multi-criteria approach helps to understand the hierarchy. The findings of this study help stakeholders prioritize the reservoirs for setting up FSP systems. Graphical abstract: Image, graphical abstract